Efektifitas Pemberian Kompos Titonia (Tithonia diversifolia) Untuk Meningkatkan Pertumbuhan Dan Hasil Tanaman Kedelai Pada Tanah Bekas Tambang Emas - Syofiani, Rika (Agrium, 2019)
The presence of activity, gold mining  causing the top layer of soil (top soil) which has high fertility mixed with other soil at the bottom which has low fertility and this can reduce productivity soil. Productivity soil can be increased by improving soil chemical properties, one of which is by adding organic material in the form of titonia compost. The purpose of this study was to obtain the correct dosage of titonia compost (Tithonia diversifolia) in the former gold mine land to increase the growth and yield of soybean plants (Glycine max L.). This study used a randomized block design (RBD) with 5 levels of treatment and 3 replications. The treatments given were without treatment (A), 10 kg of titonia compost (B), 20 kg of titonia compost (C), 30 kg of titonia compost (D) and 40 kg of titonia compost (E). The research data were statistically analyzed by the F test at 5% level. If the test results with the F test are significantly different then proceed with Duncan's Multiple Range Test (test DMRT) at a 5% significance level. The results of this study show that the administration of titonia compost (Tithonia diversifolia) 40 kg / bed improves soil chemical properties, growth and yield of soybean plants. Keywords: titonia compost, soybeans, former gold mining land.